Dermatitis artefacta: A review of five cases: A diagnostic and therapeutic challenge - Abhijit Saha; Joly Seth; Surajit Gorai; Ayush Bindal (Wolters Kluwer Medknow Publications, 2015)
Dermatitis artefacta (DA) is a self-inflicted dermatological condition where the underlying motive is to assume a sick role. The act of self-harm is to discharge the inner sense of isolation and emotional distress, which is too great to endure. We, hereby, report five interesting cases of DA with varied presentations, using diverse and innovative means for inflicting injury/injuries. Rarity may be attributed to masquerading presentation, leading to misdiagnosis and paucity of awareness among the physicians. Lack of proper identification of the underlying psychiatric disturbances may be the major cause of the loss of follow-ups. Here, we were fortunate enough to identify the emotional need of most of the patients. A flexible, nonconfrontational yet strong therapeutic rapport is required to improve the therapeutic outcomes.